State Pharmacopoeia of the Russian Federation in modern pharmaceutical analysis practice - I. A. Narkevich (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The Russian State Pharmacopoeia XIII edition assures the quality of medicines, it is important for all the stakeholders in the sphere of the circulation of medicines, ranging from pharmaceutical development to distribution of medicinal products, both for research studies and educational process. Pharmaceutical analysis plays an essential role at all stages of medicine life cycle stages. Saint-Petersburg State Chemical Pharmaceutical Academy is a main supplier of new human resources, ready to work in modern environment, including the sphere of standardization and quality control.